Development of a drug-in-adhesive patch combining ion pair and chemical enhancer strategy for transdermal delivery of zaltoprofen: pharmacokinetic, pharmacodynamic and in vitro/in vivo correlation evaluation. (21st November 2016) - Cui, Hongxia; Quan, Peng; Zhou, Zhuang; Fang, Liang
Abstract: The aim of the study was to develop a drug-in-adhesive patch system for transdermal delivery of zaltoprofen (ZAL). The formulation was designed in combination with the ion pair and chemical enhancer strategy. Seven organic amines were chosen as counter ions, and the prepared ion pairs were characterized by Fourier transform infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC). The in vivo pharmacokinetic performance of ZAL was studied on rabbits following transdermal and intravenous administration. A deconvolution method was applied to determine the correlation between the in vitro permeation and the in vivo absorption. Acetic acid-induced writhing response was conducted on mice to evaluate the analgesic effect. In vitro permeation results showed that both ion pairs and chemical enhancers were effective in modulating ZAL skin permeation from patches. The enhancement ratio was negatively correlated to the polar surface area (PSA) of counter ions, and was positively correlated to the octanol–water partition coefficient (log K o/w ) of chemical enhancers, respectively. The optimized formulation contained 10% (w/w) ZAL-triethylamine and 10% (w/w) isopropyl myristate, with DURO-TAK® 87-4098 as the pressure sensitive adhesive matrix. Furthermore, the in vitro permeation data were well correlated with the in vivo absorption data. The analgesic effect of the optimized patch was comparable to the commercial indometacin plasters. In conclusion, it was feasible for transdermal delivery of ZAL by the synergistic action of ion pair and chemical enhancer, and the in vitro permeation data were indicative of the in vivo performance for the developed patches.